Influence of IT-based organizational learning, IT-based innovation and intellectual property towards new product development performance of Yemeni food manufacturing SMEs - Jandab, Abdulwahab Ahmed Ali (2020)
Due to the highly competitive commercial environment in the market in Yemen at present, the food industry, like other industries, is under pressure to enhance their performance in terms of reducing new product development time and overall project costs, improving product quality, and satisfying customers. To keep pace with the competitive environment of the market in Yemen, most enterprises tend to adopt the best and new technologies, contemporary management concepts and philosophies such as IT (Information Technology)- based organizational learning, IT-based innovation and intellectual property (IP) to achieve improvements in the process of new product development. Current studies have referred that Yemeni manufacturing sector suffers from several issues such as limited resources in terms of finance, IT infrastructure, unskilled workforce, lack of support towards innovation orientation, and absence of intellectual property rights. This study heeded the calls for previous studies on how IT-based organizational learning can be applied within the context of new product development as it showed mixed and inconsistent findings between these combinations and more research is needed to validate these relationships. Further, the industrial survey showed a decline in the food industry performance during the past three years, due to a decrease in the growth rate, which led to a decrease in Gross Domestic Productivity, which makes initiatives and studies related to new product development an urgent national issue. This study examined empirically the effect of IT-based organizational learning, IT-based innovation, and intellectual property on new product development performance among Small and Medium Enterprises (SMEs) of the food industry. Theories of resource-based view and diffusion of innovations were utilized to test these relationships. Data were collected through self- and computer-administered questionnaires introduced to owners or managers of SMEs of Yemeni food industry. Out of 700 questionnaires distributed, 647 were returned. A total of 620 questionnaires were found usable for data analysis. Data were analyzed using Structural Equation Modelling through Smart-PLS 3.0. The findings showed that IT capability positively affect organizational learning capability. Likewise, all the dimensions of IT-based organizational learning positively affect IT-based innovation except IT human resource. The results also provided substantial support that IT-based innovation acts as a mediator on the relationships between the dimensions of IT-based organizational learning and new product development performance except IT human resource. As for IP, the finding revealed an insignificant moderating effect of intellectual property in the relationship between IT-based innovation and new product development performance. This study contributes to new knowledge of evaluating a model of IT-based organizational learning, IT-based innovation, and intellectual property with new product development performance, particularly in the Yemeni context. Practically, the study can also serve as a guide for owners and managers of SMEs, on the importance of ITbased organizational learning, IT-based innovation and intellectual property toward achieving better new product development performance and competitiveness.